2016
DOI: 10.1017/s0022215116001043
|View full text |Cite
|
Sign up to set email alerts
|

Emergency presentations of head and neck cancer: a modern perspective

Abstract: Emergency presentations are increasing annually. Female patients and oropharyngeal cancer showed greater representation compared to male patients and laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…Patients with laryngeal cancer are more likely to develop emergent symptoms that affect their respiratory status, prompting emergency department visitation. Other subsites and associated complications of treatment are also more amenable to patient‐directed surveillance and outpatient management, whereas laryngeal cancer is difficult to monitor and treat without direct or indirect laryngoscopy …”
Section: Discussionmentioning
confidence: 99%
“…Patients with laryngeal cancer are more likely to develop emergent symptoms that affect their respiratory status, prompting emergency department visitation. Other subsites and associated complications of treatment are also more amenable to patient‐directed surveillance and outpatient management, whereas laryngeal cancer is difficult to monitor and treat without direct or indirect laryngoscopy …”
Section: Discussionmentioning
confidence: 99%
“…[2] With changing epidemiology, a study from the United Kingdom has noted that the oropharynx is the most common site among the patients presenting to ED. [6]…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results of this study, dysphagia was the most common reason for reporting to the ED in the UK, whereas respiratory infections was the most common cause in North America. [46] This variation could be because of oropharyngeal and laryngeal cancer being the most common in those cohorts. A study from Taiwan too showed ill-defined complaints being the most common presentation of HNC patients coming to ED.…”
Section: Discussionmentioning
confidence: 99%
“…2 Bannister and colleagues' article from Scotland demonstrates an increase in emergency presentations of head and neck cancer cases, particularly oropharyngeal cancer, which is not easily explained at present. 3 There is certainly room for improvement in generating confidence among junior doctors in basic emergency skills in ENT, particularly in the accident and emergency department. 4 There is much folklore about what makes someone enter a particular specialty, the caricature cardiac surgeon being somewhat different from the caricature psychiatrist.…”
mentioning
confidence: 99%
“…One such idea is a well set up emergency clinic, which was covered in a recent article in relation to the importance of senior cover in such clinics 2 . Bannister and colleagues' article from Scotland demonstrates an increase in emergency presentations of head and neck cancer cases, particularly oropharyngeal cancer, which is not easily explained at present 3 . There is certainly room for improvement in generating confidence among junior doctors in basic emergency skills in ENT, particularly in the accident and emergency department 4 …”
mentioning
confidence: 99%